"We're talking about black men here, there's a difference"; cultural differences in socialised knowledge of prostate cancer risk: A qualitative research study. (February 2022) - Fry, Sarah Louise; Hopkinson, Jane; Kelly, Daniel
Abstract: Purpose: To detail social knowledge of prostate cancer risk amongst cultural groups. Prostate cancer is the most common cancer in men, and black men are at the highest risk. Despite this, black men are the least likely to be diagnosed early with prostate cancer. It is important to understand why this is so that these men can receive early access to effective treatment and support. Methods: A constructivist grounded theory methodology was used. Data were collected between December 2015 and October 2017; seventeen men were interviewed, and eighteen men took part in focus groups. Results: There were differences in the way the men constructed their understanding of risks for prostate cancer. The social construction of prostate cancer risk knowledge was mediated by the way the men were socialised to understand and accept this risk. The Somali and African Caribbean men placed social importance on the healthy body, whereas the white working class men seemed to find social value through the unwell body. This research proposes the theory that social constructions of knowledge mediate the way men perceive and accept their risk for prostate cancer. Conclusion: Understanding socially-derived knowledge of risk may mediate the acceptance of factors relating to prostate cancer. This knowledge may help health providers and third sector organisations produce targeted health-related information. Health practitioners may also benefit from understanding how socially constructed ideas of the body could influence the way men respond to conversations about prostate cancer so that tailored and culturally appropriate support can be offered. Highlights: This paper presents data from research conducted with men without prostate cancer, to offer insights into how these men understand their risk for this particular cancer. This research is distinctive in focusing on the differences in social understanding of prostate cancer between cultural groups. This paper suggested ways healthcare professionals may consider their approach to education of prostate cancer risk, based on socially constructed cultural knowledge.